The Relationship Between Human Resource Management Practices and Organizational Creativity: A Case Study of the Al-Jumhouria Bank in El Marg City - Murad Abdulqader Abdulmawla Saleh (Journal of Libyan Academy Bani Walid, 2025)
This study aimed to test the relationship between human resource management practices and organizational creativity at the Bank of the Al-Jumhouria, in its two branches (Al-Jalaa, Al-Salfioum) in the city of Al-Marj. The study followed a descriptive analytical approach and used a comprehensive enumeration method for a total of (52) bank employees. Primary data for the study were collected using a questionnaire, and analyzed with the statistical program SPSS. The study results showed that human resource management practices at the Bank of the Al-Jumhouria in Al-Marj are implemented at a high level, and organizational creativity was also recorded at a high level. The results indicated that there is a positive, moderate, and highly significant correlation between human resource management practices and organizational creativity at the Bank of the Al-Jumhouria in Al-Marj. The study recommended maintaining the policies followed by the Bank of the Al-Jumhouria in recruitment and hiring, and continuing to conduct training programs at the bank in accordance with technological changes in the global environment